X‐ray fluorescence spectroscopy and Monte Carlo simulation for quantitative characterization of Bolivian pre‐Hispanic golden artefacts. (18th September 2020) - Melquiades, Fabio L.; Santos, Sandro V.; Lopes, Fabio; Villanueva, Juan; Ticona, Jorge L.; Appoloni, Carlos R.
Abstract : The quantification of archaeological artefacts with X‐ray Fluorescence is quite complex because it demands some calibration procedure. It is also rather more challenging when the customization of the portable equipment for in situ measurements is required. The objective of this study was to introduce a quantitative method by performing a calibration curve for a ternary gold alloy (Au, Ag and Cu). Fast Monte Carlo simulation combined with in situ portable XRF (pXRF) measurements in order to circumvent the calibration requirement using standard reference materials was used. Measurements with a laboratory‐made equipment were taken from a set of 16 pre‐hispanic gold alloy artefacts of a collection from the Museo Nacional de Etnografia y Folklore, La Paz, Bolivia. The spectra simulation was conducted with the XMI‐MSIM software.The results demonstrated that the combined use of pXRF measurements and spectra simulation via Monte Carlo is a feasible method for gold alloy quantification. In the examined samples, the Cu content was below 5% and for Au it ranged from 13 to 100%. Moreover, some peculiarities of the artefacts archaeological context were discussed.